102k views
8 votes
If 3x − (7 − x) = 29, find the value of 6x.

Hint:

Rewrite 3x − (7 − x) as

3x + −1(7 − x)

and then use the Distributive Property to simplify.

6x = 45

6x = 60

6x = 46

6x = 54

2 Answers

6 votes

Answer:

54

Explanation:

3x -(7-x) = 29

3x - 7 + x = 29

4x -7 = 29

4x = 36

x = 9

6x = 6 x 9

6 x 9 = 54

User Vedanshu
by
4.7k points
10 votes

Answer:

54

Explanation:

3x -(7-x) = 29 remove the parens

3x - 7 + x = 29 simplify

4x -7 = 29 add 7 to both sides of the equation

4x = 36 divide by

x = 9

then 6x = 6 * 9 = 54

User Kikon
by
5.3k points